Co-utilization of lake sediment and blue-green algae for porous lightweight aggregate (ceramsite) production. (January 2022) - Zhao, Lina; Hu, Min; Muslim, Halimi; Hou, Tianyang; Bian, Bo; Yang, Zhen; Yang, Weiben; Zhang, Limin
Abstract: Lake sediment and algal sludge with large output posed significant environmental risks. In this work, an idea of co-utilization of both solid wastes for the production of ceramsite (a sort of porous lightweight aggregates as building materials) was proposed and validated for the first time. The treatment process contained a dewatering step by a flocculation-pressure filtration method, and a sintered ceramsite preparation step. Effects of flocculant type and dosage on the dewatering performance were studied in the first step. An environmental-friendly amphoteric starch flocculant with a dosage of 12 mg/(g dried sample) was found to achieve the best dewatering performance. Effects of raw material mass ratio, sintering temperature and time in the second step were investigated. Under the optimal conditions (60 wt% of dewatered sediment; 20 wt% of dewatered algal sludge; 20 wt% of additives (fly ash: calcium oxide: kaolin = 2:1:2); sintering temperature: 1100 °C; time: 35 min), the obtained ceramsite met the Chinese National Standard as a qualified building material, with reliable environmental safety according to the leaching results for both heavy metals and microcystins. Both environmental and economic benefits of the proposed treatment were assessed. The process completely followed the rules of "reduction, harmlessness and resource utilization" for solid waste treatment and disposal; Meanwhile, the profit of the proposed ceramsite production could be more than 2.3 US dollar/m 3 . The co-utilization method in this work acted as a good example for the comprehensive management of solid wastes in water-rich areas. Graphical abstract: Image 1 Highlights: Co-utilization of lake sediment and algal for ceramsite production is assessed. Solid wastes are dewatered using amphoteric starch flocculant (12 mg/g dry sample). Optimal ratio of dewatered sediment, algal sludge and inorganic additives is 3:1:1. Optimal sintering conditions for qualified ceramsite are 1100 °C and 35 min. Leaching risks of heavy metals and microcystins are significantly reduced.